Identification of a new protein localized at sites of cell-substrate adhesion (The Rockefeller University Press, 1986)
A new protein found at sites of cell-substrate adhesion has been identified by analysis of a nonimmune rabbit serum. By indirect immunofluorescence this serum stains focal contacts (adhesion plaques) and the associated termini of actin filament bundles in cultured chicken cells. Western immunoblot analysis of total chick embryo fibroblast protein demonstrated an 82-kD polypeptide to be the major protein recognized by the unfractionated serum. This 82-kD protein is immunologically distinct from other known adhesion plaque proteins such as vinculin, talin, alpha-actinin, and fimbrin. Antibody affinity- purified against the electrophoretically isolated, nitrocellulose-bound 82-kD protein retained the ability to stain the area of the adhesion plaque, which confirms that the 82-kD protein is indeed a constituent of the focal contact. The 82-kD polypeptide has a basic isoelectric point relative to actin and fibronectin, and it appears to be very low in abundance. The 82-kD protein is ubiquitous in chicken embryo tissues. However, it appears to be more abundant in fibroblasts and smooth muscle than in brain or liver. Intermediate levels of the protein were detected in skeletal and cardiac muscle. The subcellular distribution of the 82-kD protein raises the possibility that this polypeptide is involved in linking actin filaments to the plasma membrane at sites of substrate attachment or regulating these dynamic interactions.